Dust and Ice in the Interstellar Medium - Ochmas, Nastaran (Journal for Research in Applied Sciences and Biotechnology, 2024)
In this paper, we present an introduction to bare dust particles and grains covered by ice sheets in diffuse and dense interstellar clouds. It follows the life cycle of dust from its formation in stellar environments to its incorporation into the body of the Solar system. Dust particles play an important role in the physics and chemistry of many space environments. Regarding dust composition, two different populations are generally observed: silicate and carbonaceous dust. Energetic processing of ice layers with UV rays, X – rays or cosmic rays, after which the heat leads to the formation of complex organic molecules; some of them have prebiotic properties. Delivery of this organic fraction to the early Earth by meteorites and asteroids may have contributed to the origin of life.